IBD 8 Perceptions of Young People with Inflammatory Bowel Disease and their Parents/Carers regarding a Digital Personal Health Record. (12th September 2022) - Yeop, Intan; Howsley, Philippa; Hansen, Richard; Lee, Margaret; Epstein, Jenny; Narula, Priya
Abstract : Objectives: Digital personal health records (DPHR) have great potential to empower and equip young people (YP) to effectively manage their health condition. This study aimed to understand the views, requirements and concerns of YP with Inflammatory Bowel Disease (IBD) and their parents/carers regarding a developmentally appropriate and user-friendly DPHR. Design: Sheffield Children's NHS Foundation Trust, NIHR Children and Young People MedTech Co-operative and Crohn's in Childhood Research Association (CICRA) collaborated to develop and circulate YP and parent/carer versions of the survey to all YP and parents registered with CICRA. Survey respondents were given the options of 'yes, no or maybe' in answer to the questions, with the opportunity of commenting on each question in the free text sections. Questions included were 'Do you think it would be helpful if the app had alerts to remind you about your hospital appointments?' and 'What is your opinion of the app? 0=dislike, 100=like'. Responses were collected between January and February 2021. Results: 25 YP (9–25 years (median 14); 64% female) and 93 parents/carers (44% female) across the UK completed the survey. Both YP and parents/carers rated the idea of the DPHR highly (YP: n=25, median 90(51–100)%; parents: n=86, median 100(4–100)%). YP and parents/carers would like easy access to information on IBD (YP:80%, parents/carers:89%) for themselves and to share with friends, family and teachers. Information about the transition process (YP:88%, parents/carers:97%), and information and contact details for the paediatric (YP:88%, parents/carers:95%) and adult (YP:88%, parents/carers:97%) clinical teams were felt to be helpful in supporting YP during this important period. The majority of YP and parents/carers would like access to their personal clinical records (YP:96%, parents/carers:89%), medication lists (YP:96%, parents/carers:95%), clinical laboratory results (YP: 84%, parents/carers:89%), endoscopy reports (YP:84%, parents/carers:84%), radiology reports (YP:76%, parents/carers: 84%) and hospital appointments (YP:96%, parents/carers:99%). They would also like information on emotional wellbeing (YP:80%; parents:92%), nutrition and diet (YP:60%; parents:87%), preparation for endoscopic procedures (YP:76%; parents:80%), medications and treatments (YP:84%; parents:86%), travel information (YP:84%; parents:93%) and research opportunities (YP:52%; parents:66%). YP and parents/carers would like interactive features such as symptom tracking function and disease activity indices (YP:84%; parents:88%). Most of the participants would also like the app to provide alerts and notifications for hospital appointments (YP:80%; parents:90%) and blood monitoring appointments (YP:80%; parents:82%). From the general comments made on a proposed DHPR, YP and parents/carers viewed knowledge on IBD positively and felt that it would be a useful tool to encourage YP involvement in their own care. Some parents/carers would like the ability to regulate the information accessed by their child to ensure that the information and functions are age-appropriate. Conclusion: A DPHR would be welcomed by the majority of YP with IBD and their parents/carers. Further co-design with YP, parents/carers, and clinical teams is needed to understand the exact requirements of the app and its design, and to explore potential concerns.